2016
DOI: 10.1097/ceh.0000000000000111
|View full text |Cite
|
Sign up to set email alerts
|

Exploratory Study of Rural Physicians' Self-Directed Learning Experiences in a Digital Age

Abstract: DSMTs are growing in popularity as a key resource to support SDL for rural physicians. Mobile technologies are enabling greater "point-of-care" learning and more efficient information seeking. Effective use of DSMTs for SDL has implications for enhancing just-in-time learning and quality of care. Increasing use of DSMTs and their new effect on SDL raises the need for reflection on conceptualizations of the SDL process. The "digital age" has implications for our CPD credit systems and the roles of CPD providers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The second most reported disadvantage was poor design (19%, n = 53), including lack of interaction (between learner and facilitator or between learners); 34 , 51 , 59 , 67 , 70 , 77 , 79 , 84 , 88 , 90 , 104 , 112 , 123 , 135 , 142 , 168 , 208 , 216 , 224 , 239 , 243 , 251 - 256 lack of active participation; 33 , 125 , 159 , 232 , 237 , 257 , 258 logistical issues (e.g., microphone and camera placement, unmuted microphones) 36 , 58 , 59 , 110 , 174 , 232 , 236 , 259 and technology-related logistical issues (e.g., site blocked by institution); 31 , 33 , 59 , 60 , 108 , 117 , 149 , 177 , 187 , 202 , 228 , 259 not user-friendly; 34 , 59 , 66 , 149 , 208 , ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second most reported disadvantage was poor design (19%, n = 53), including lack of interaction (between learner and facilitator or between learners); 34 , 51 , 59 , 67 , 70 , 77 , 79 , 84 , 88 , 90 , 104 , 112 , 123 , 135 , 142 , 168 , 208 , 216 , 224 , 239 , 243 , 251 - 256 lack of active participation; 33 , 125 , 159 , 232 , 237 , 257 , 258 logistical issues (e.g., microphone and camera placement, unmuted microphones) 36 , 58 , 59 , 110 , 174 , 232 , 236 , 259 and technology-related logistical issues (e.g., site blocked by institution); 31 , 33 , 59 , 60 , 108 , 117 , 149 , 177 , 187 , 202 , 228 , 259 not user-friendly; 34 , 59 , 66 , 149 , 208 , ...…”
Section: Resultsmentioning
confidence: 99%
“… 277 It has also led to record attendance numbers in participants and experts that were not previously possible with in-person conferences. 179 Although most VCME activities were focused on general/family practitioners, VCME focused on specialties such as oncology, sports medicine, and plastic surgery have also been positively received, 77 , 174 , 236 suggesting that the benefits of VCME may not be limited by medical specialty. Although we did not detect meaningful differences in gender regarding the convenience of VCME, it should be noted that only fewer than one-third of articles that mentioned convenience as an advantage of CME reported on participants’ gender.…”
Section: Country Of Origin Of Vcmementioning
confidence: 99%
“…Apart from one study of uncertain quality that reported better outcomes for e-learning compared to face-to-face learning or use of text-based learning [ 29 ], this systematic review found good quality evidence that there is little to no difference between e-learning and other CPD approaches [ 25 28 ]. CPD using an e-learning approach has increased during the pandemic [ 72 76 ] and is also an important strategy for rural practitioners [ 77 , 78 ].…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Self-directed learning in a digital age is also a growing phenomenon with implications for both the learning process and learner attributes (Curran et al, 2017;Fahlman, 2013;Scott et al, 2014). The importance of digital, social, and mobile technologies is also growing within the field of continuing education in the health professions (Curran, Fleet, Simmons, Ravalia, & Snow, 2016;Curran et al, 2017). Mobile technology use among health professionals is increasing and enables greater levels of professional interaction and communications, enhanced convenience and efficiency, and introduces more flexible opportunities for lifelong learning (Bacigalupe, 2011;Baumgart, 2017;Boruff & Storie, 2014;O'Connor et al, 2014;Robinson et al, 2013;Sclafani, Tirrell, & Franko, 2013;Wang, Sandhu, Wittich, Mandrekar, & Beckman, 2012).…”
Section: Introductionmentioning
confidence: 99%